A voyage for whaling and discovery, round C. Horn into the Pacific Oceans - Colnett, James (Adam Matthew Digital, 1793)
Ms journal of James Colnett's voyage in the Rattler, round Cape Horn into the Pacific Ocean, 1793-1794